Transiting exoplanets from the CoRoT space mission - Almenara, J; Bouchy, F; Gaulme, P; Deleuil, M; Havel, M; Gandolfi, D; Deeg, H; Wuchterl, G; Guillot, T; Gardes, B; Pasternacki, T; Aigrain, S; et al. (2013)
We report the discovery of two transiting exoplanets, CoRoT-25b and CoRoT-26b, both of low density, one of which is in the Saturn mass-regime. For each star, ground-based complementary observations through optical photometry and radial velocity measurements secured the planetary nature of the transiting body and allowed us to fully characterize them. For CoRoT-25b we found a planetary mass of 0.27 ± 0.04 MJup, a radius of 1.08 -0.10+0.3 RJup and hence a mean density of 0.15-0.06+0.15 g cm-3. The planet orbits an F9 main-sequence star in a 4.86-day period, that has a V magnitude of 15.0, solar metallicity, and an age of 4.5-2.0+1.8-Gyr. CoRoT-26b orbits a slightly evolved G5 star of 9.06 ± 1.5-Gyr age in a 4.20-day period that hassolar metallicity and a V magnitude of 15.8. With a mass of 0.52 ± 0.05 MJup, a radius of 1.26-0.07+0.13 RJup, and a mean density of 0.28-0.07+0.09 g cm-3, it belongs to the low-mass hot-Jupiter population. Planetary evolution models allowed us to estimate a core mass of a few tens of Earth mass for the two planets with heavy-element mass fractions of 0.52 -0.15+0.08 and 0.26-0.08+0.05, respectively, assuming that a small fraction of the incoming flux is dissipated at the center of the planet. In addition, these models indicate that CoRoT-26b is anomalously large compared with what standard models could account for, indicating that dissipation from stellar heating could cause this size. © 2013 ESO.